MORPHOLOGICAL CHARACTERIZATION OF THE AFRICAN CATFISH (Clarias gariepinus BURCHELL, 1822) STRAINS INTRODUCED TO INDONESIA - Bambang Iswanto; Imron Imron; Rommy Suprapto; Huria Marnis (Indonesian Aquaculture Journal, 2015)
African catfish (Clarias gariepinus Burchell, 1822) has become a great important species in Indonesian aquaculture. Several strains of the African catfish have been introduced to Indonesia for aquaculture purposes, initiated by Dumbo strain from Taiwan in 1985, followed by Paiton strain from Thailand in 1998, then Egypt strain from Egypt in 2007, Masamo strain from Thailand in 2010 and later Kenya strain from Kenya in 2011. Since its introductions, there were no reports yet on their characterization studies. The present study was conducted to morphologically characterize the strains of African catfish introduced to Indonesia, i.e. Dumbo, Paiton, Egypt, Masamo, and Kenya strains. Morphometric and meristic data obtained were analyzed using Principal Component Analysis. Results of the morphometric characterization in the present study revealed that Dumbo, Paiton, Masamo, and Kenya strains were indistinguishable, while morphometric characteristic of Egypt strain was more or less different from those of the other strains. On the other hand, results of the meristic characterization suggested that meristic characteristics of all strains of the introduced African catfish were not different from each other. Therefore, to keep the genetic purity of those introduced strains, they should be properly maintained in isolated places.